Psychometric validation of the Carers of Older People in Europe Index among family caregivers of older persons with dementia. (August 2018) - Moholt, Jill-Marit; Friborg, Oddgeir; Skaalvik, Mari Wolff; Henriksen, Nils
Objectives: The Carers of Older People in Europe Index is a first-stage assessment tool to detect family caregivers in need of support. This instrument assesses caregivers' subjective perceptions of their caregiving circumstances. The present study examines the psychometric properties of the Norwegian version of the Carers of Older People in Europe Index among family caregivers for older persons with dementia living at home. Methods: Cross-sectional survey data were collected from 430 dementia caregivers. The sample was randomly split as follows: the first half of the sample was used to identify the measurement model using an exploratory factor analysis, and the second half of the sample was used to cross-validate the model using a confirmatory factor analysis. The criterion validity and reliability (internal consistency and test–retest reliability) of the Carers of Older People in Europe Index were also examined. Results: Using an exploratory factor analysis, we extracted three factors that were consistent with previous findings: negative impact of caregiving, positive values of caregiving and quality of support. This model fit the data well using a confirmatory factor analysis. Moreover, a second-order model could replace the three-factor correlated model without sacrificing the model fit, supporting the use of a global impact of caregiving score. The three factors and the global factor correlated with the criteria measures in the expected directions. The internal consistency was assessed using Cronbach's alpha and was good for the negative impact ( α  = 0.86) and the quality of support ( α  = 0.76) factors. The positive values factor was less consistent ( α  = 0.64). The test–retest reliability was examined using Spearman's rank order correlation and was good for all three factors. Conclusion: The psychometric properties of the Norwegian version of the Carers of Older People in Europe Index are good. The instrument assesses dementia caregivers' situations across three primary factors or alternatively validly summarizes the factors in a global impact of caregiving score.